Experimental evaluation of the possibility of determining bacterial endotoxins in typhoid Vi polysaccharide vaccines using the gel-clot test - M. V. Abramtseva; N. S. Alekhina; E. D. Kolyshkina (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Scientific relevance. Currently, only the rabbit pyrogen test is used to test the Vianvac® typhoid Vi polysaccharide vaccine for pyrogenicity. As part of the product specification file, the gel-clot test for bacterial endotoxins (BE) will improve the reliability of quality control, as well as harmonise the requirements for the vaccine with the requirements outlined for this group of medicinal products by leading world pharmacopoeias.Aim. This study aimed at an experimental assessment of the applicability of the gel-clot test to the quantification of BE in the typhoid Vi polysaccharide vaccine.Materials and methods. This study used samples from 5 batches of the typhoid Vi polysaccharide vaccine (0.5 mL/dose, solution for subcutaneous injection), LAL and TAL reagents. The analysis included the gel-clot test and the pyrogenicity test according to the State Pharmacopoeia of the Russian Federation (OFS.1.2.4.0006.15 and OFS.1.2.4.0005.15, respectively).Results. According to calculations, the BE limit for the tested vaccine was 96 EU/mL, and the maximum valid dilution (MVD) was 3200. The authors determined the regulatory requirements for typhoid Vi polysaccharide vaccine quality in terms of BE (not more than 48 EU/dose). The in vitro BE tests were positive at vaccine dilutions of 1/16 to 1/32 and negative at 1/64 to 1/256. The authors selected and validated a working vaccine dilution of 1/128. The BE content measured in the tested samples ranged from 0.24 to 0.48 EU/dose. The in vivo pyrogen tests were positive at dilutions of 1/16 to 1/128 and negative at 1/256 in all experiments with samples from 5 vaccine batches at dilutions ranging from 1/16 to 1/256.Conclusions. This study has experimentally proven that the gel-clot test can quantify BE in the typhoid Vi polysaccharide vaccine. The authors have recommended introducing the gel-clot BE test in the monograph of the State Pharmacopoeia of the Russian Federation on the typhoid Vi polysaccharide vaccine (FS.3.3.1.0012.15).